Post-pandemic reconfiguration from global to domestic and regional value chains: the role of industrial policies - Stefano Elia; Luciano Fratocchi; Paolo Barbieri; Albachiara Boffelli; Matteo Kalchschmidt (Transnational Corporations, 2021)
The COVID-19 pandemic is expected to trigger a reconfiguration of global value chains according to four alternative trajectories: reshoring, regionalization, replication and diversification. This paper focuses on the first two scenarios. On the basis of a review of the extant reshoring literature and policies implemented in several major developed and emerging economies, we present a comprehensive framework to classify and analyse the evolution of such policies before and after the pandemic. The paper develops some policy recommendations suggesting that reshoring policies need to be supported by and combined with industrial policies enforcing the competitiveness and sustainability of production systems.